2018
DOI: 10.1002/dc.24120
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of fine‐needle aspiration cytology of head and neck masses

Abstract: Background Head and neck masses are a common presentation in daily practice and can be challenging to both clinicians and cytopathologists. Fine needle aspiration cytology (FNAC) is a widely used method for the diagnosis of head and neck masses. The aim of the study was to assess our institutional experience of the accuracy of FNAC in the diagnosis of head and neck masses. Methods A total of 1262 FNACs were conducted from January 2013 to December 2016 and subdivided into benign and malignant categories. The th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 28 publications
3
24
1
Order By: Relevance
“…According to the literature, it represents the first and most useful diagnostic tool in the evaluation of several body lesions. In fact, among the others, it has demonstrated interesting results in terms of diagnostic accuracy in head and neck cancer, breast carcinoma, and cervical carcinoma . To date, only 2 studies, from the same institution, have been published on the diagnostic utility of ultrasound with guided FNAC in the assessment metastatic lymph node disease in vulvar carcinoma.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…According to the literature, it represents the first and most useful diagnostic tool in the evaluation of several body lesions. In fact, among the others, it has demonstrated interesting results in terms of diagnostic accuracy in head and neck cancer, breast carcinoma, and cervical carcinoma . To date, only 2 studies, from the same institution, have been published on the diagnostic utility of ultrasound with guided FNAC in the assessment metastatic lymph node disease in vulvar carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, among the others, it has demonstrated interesting results in terms of diagnostic accuracy in head and neck cancer, breast carcinoma, and cervical carcinoma. [10][11][12][13][14] To date, only 2 studies, from the same institution, have been published on the diagnostic utility of ultrasound with guided FNAC in the assessment metastatic lymph node disease in vulvar carcinoma. Moskovic et al, in their pilot study on 21 patients with early vulvar carcinoma using ultrasound and FNAC, confirmed an overall sensitivity of 83% and specificity of 82% for the detection of groin lymph node metastases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As reported in literature, FNAC has a high sensitivity (72.4-100%), a high specificity (85.3-100%) as well as a high accuracy (73.3-98.0%) [1]. However, certain rates of non-diagnostic or inconclusive results have also been reported [2,3]. In case of a non-diagnostic result, the sample contains not enough cells, or it was contaminated by blood cells.…”
Section: Introductionmentioning
confidence: 94%